P389 Switching infliximab to subcutaneous from intravenous therapy (SWIMSUIT) – A prospective, real-world, single centre, phase IV interventional study. (30th January 2023) - Rahmany, S; Young, D; Moyses, H; Gonclaves, J; Latter, S; Cummings, F
Abstract: Background: Subcutaneous (SC) infliximab (CT-P13) was approved in 2020 by the EMA for use in IBD. This offers patients greater choice, flexibility and the convenience of administering their treatment at home as well as other potential therapeutic benefits. We aim to evaluate the clinical outcomes of patients switching from intravenous (IV) infliximab to SC CT-P13. Methods: We offered IBD patients established on IV infliximab (>4 doses) the opportunity to switch to SC CT-P13. Patients who agreed to switch were followed up every 12 weeks for 24 weeks. Demographics, disease history, disease activity scores, IBD CONTROL PROM, SF36, calprotectin, standard blood tests, infliximab drug levels, antidrug antibodies (ADA) and adverse events were collected at each visit. The primary endpoint was the maintenance of clinical status at week 24 (W24). A failure to maintain clinical status was defined as an increase in disease activity scores (mHBI or SCCAI) of ≥3, and/or a decline in IBD-Control PROM score of ≥4 points at any time during the study period. Results: We approached 204 patients receiving IV infliximab, of which 120 patients switched to SC CT-P13 (75.8% CD, 22.5% UC, 1.7% IBDU). 24 patients had perianal disease at baseline. Median age was 38. The median time taken by patients (leaving home to returning home) to receive their infusions was 180 minutes (range 60 to 660). 96 participants were on concomitant immunomodulators (79 thiopurines, 17 methotrexate) and 105 were treated with SB2 preswitch. The median duration of IV infliximab prior to switching was 45 months. 70 (58%) of the patients were on the standard dosing (5mg/kg Q8W) regimen. All patients were switched to 120mg of SC CT-P13 every other week, regardless of their baseline regimen. 11 (9.2%) patients discontinued the treatment prior to finishing the study. 75% (CI 0.65, 0.82) of the whole cohort reached the primary endpoint of maintaining clinical status at week 24. There was no statistically significant difference in disease activity scores or IBD-Control PROM between baseline and W24. 31 (25.8%) of the patients had evidence of immunogenicity at baseline (ADA of > 50ng/ml). Of the 89 patients with no immunogenicity at baseline, 69 (77.5%) maintained this at W24. The median serum infliximab levels increased by 72.8 % from baseline to W24 (3.05 µg/ml to 5.27 µg/ml (figure 1)). Median ADA levels increased from 8.46 ng/ml at baseline to 10.6 ng/ml at W24 (figure 2). Patient satisfaction with SC CT-P13 was very high (figure 3). Conclusion: Switching patients from IV to SC CT-P13 is safe, effective, and well-accepted with higher infliximab serum levels. The majority of the patients with no immunogenicity at baseline maintained this at W24.